Underpinning data "A comprehensive study of factors affecting postharvest disorder development in celery ". - Anastasiadi, Maria; Falagán, Natalia; Rossi, Simone; Terry, Leon A. (Cranfield University, 2020)
This dataset contains the data used for statistical analysis in the paper entitled "A comprehensive study of factors affecting postharvest disorder development in celery". Specifically it contains physiological and biochemical changes affecting quality, during shelf-life in celery plants from three different horticultural maturity stages and harvested in different seasons from Spain and the UK. Part of the samples were subjected to different postharvest treatments: 1-MCP application for 24 h followed by cold storage storage under continuous air, continuous ethylene application, and continuous air application (control). In addition, this dataset contain data recording the physiological and biochemical changes occurring during shelf-life in celery plants grown under deficit irrigation and harvested at different horticultural maturity stages. Physiological changes recorded include, respiration rate, objective colour, dry matter changes, browning development and pithiness development. Biochemical data include individual sugars, abscisic acid and its catabolites and chlorogenic acid. Also the data capture spatial differences along the celery plants (apical and basal regions).
Keywords: Apium graveolens'; 'physiological disorders'; 'horticultural maturity'; 'deficit irrigation'; 'abscisic acid content'; 'Post Harvest Horticultural Technologies (incl. Transportation and Storage)'